Rapid detection of polymorphisms of the nitric oxide cascade - Weiß, Johanna; Fricker, Ruth; Haefeli, Walter E. (Clinical chemistry and laboratory medicine, 2002)
NOS3 (endothelial nitric oxide (NO) synthase) and p22phox (subunit of NAD(P)H oxidase) are two genes whose products are involved in formation and degradation of NO, a ubiquitous signaling molecule largely responsible for the maintenance of normal endothelial function. The G894T polymorphism of NOS3 and the C242T polymorphism of p22phox are reportedly associated with numerous cardiovascular diseases. For each polymorphism we developed a rapid and reliable method with the hybridization probes format on the Lightcycler TM and compared it with conventional PCR-restriction fragment length polymorphism (PCR-RFLP) analysis with regard to reliability, duration and cost. The new methods are more reliable, faster and less expensive than PCR-RFLP analysis and therefore represent a significant advantage in the detection of two candidate risk factors for cardiovascular diseases.